2011
DOI: 10.1089/jmf.2009.0192
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed but Not Flaxseed Oil Prevented the Rise in Serum Cholesterol Due to Ovariectomy in the Golden Syrian Hamsters

Abstract: This study was designed to investigate whether flaxseed oil (FO) exerts hypocholesterolemic effects similar to ground whole flaxseed (WF) and to gain insight into its hypocholesterolemic mechanism. Forty-eight 6-month-old female Golden Syrian hamsters were either sham-operated (Sham) or ovariectomized (Ovx) and randomly assigned to one of four treatment groups (n = 12/group) for 90 days: Sham, Ovx, Ovx+WF, or Ovx+FO. Hamsters in the Sham and Ovx groups were fed a semipurified diet (control), whereas Ovx+WF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…As reported previously ( 37 ) , Ovx rats had significantly higher plasma TC concentrations than sham-operated rats following the SD. Unexpectedly, this difference between the Ovx and sham-operated animals was entirely abolished after consumption of the HF and HFHC diets.…”
Section: Discussionsupporting
confidence: 87%
“…As reported previously ( 37 ) , Ovx rats had significantly higher plasma TC concentrations than sham-operated rats following the SD. Unexpectedly, this difference between the Ovx and sham-operated animals was entirely abolished after consumption of the HF and HFHC diets.…”
Section: Discussionsupporting
confidence: 87%
“…[31] Addition of flaxseeds to the diet partially mitigated the rise in circulating cholesterol levels induced by the cholesterol-enriched diet through its content of ALA. [32] The results of our study are further supported by the findings of another study which proposes that increased bile acid synthesis is one of the major cholesterol-lowering mechanisms of flaxseed and that another component, besides its oil, contributes to its hypocholesterolemic property. [33] Dietary flaxseed lignans, such as secoisolariciresinol diglucoside (SDG), also have demonstrated potent antioxidant and anti-atherogenic effects. [34] A simultaneous mean elevation of 4.94% in the serum HDL level was also observed in our study [ Table 4].…”
Section: Resultsmentioning
confidence: 99%
“…4 Flaxseed oil did not prevent the rise in TC in ovariectomized Syrian hamsters although flaxseed did prevent this rise. 43 Nounou et al 44 showed that myocardial ischemia in rats increases the serum levels of TC and TG, decreases the serum level of LDL-C, and has no effect on HDL-C. In their study, they showed that flaxseed oil (0.4 g/kg daily for 6 weeks) reduced the serum levels of TG, TC, and LDL-C, but had no effect on HDL-C in rats with myocardial ischemia.…”
Section: Flaxseed Oil and Lipid Reduction Animal Studiesmentioning
confidence: 97%